Improving 3D Animation Education: A Case Study of Curriculum Development in Jordan - Marar, Rosana; Alhyari, Narmeen; Tedmori, Sara (International Journal of Engineering Pedagogy (iJEP), 2025)
This study explores the various factors that influence the development of 3D animation skills, focusing on the role of acting skills, instructor feedback, and the understanding of emotions in improving students’ animation outcomes. The primary goal is to propose methods for enhancing the pedagogy of 3D animation subjects. This study adopts a quantitative research design, analyzing the grades of 97 students and the responses to a survey administered to 50 students. Descriptive, correlation, and regression analyses are employed. Findings from our quantitative analysis indicate a strong positive correlation between students’ acting skills and the produced quality of animation and a moderate positive correlation between observing human emotion and improved acting skills. These findings highlight the importance of integrating acting techniques into the animation curricula. The study offers actionable insights to improve 3D animation curricula and enhance the educational practices in 3D animation, leading to the development of professional animators.